2017
DOI: 10.1002/kin.21068
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue/NaNO2as an Efficient Reagent for the Nitration of Phenols in Aqueous Bisulfate and Acetonitrile Medium: Synthetic and Kinetic Study

Abstract: The reaction kinetics of Prussian blue (PB)/NaNO2 initiated for the nitration of phenols by in aqueous bisulfate and acetonitrile medium indicated first‐order dependence on [phenol], [NaNO2], and [PB]. An increase in [KHSO4] accelerated the rate of nitration under otherwise similar conditions. The rate of nitration was faster in the solvent of higher dielectric constant (D). Observed results were in accordance with Amis and Kirkwood plots [log k′ vs. (1/D) and [(D − 1)/(2D + 1)]. These findings together with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Reaction rates accelerated with the following sequence: p −Me> m −Me>H> o −OH> m ‐OH> m −Cl due to the electron donating groups. Selective method for nitration of phenol and use of eco‐friendly catalyst under mild condition make this approach wide synthetic with commercial utility [48] …”
Section: Nitration By Transition Metal‐free Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction rates accelerated with the following sequence: p −Me> m −Me>H> o −OH> m ‐OH> m −Cl due to the electron donating groups. Selective method for nitration of phenol and use of eco‐friendly catalyst under mild condition make this approach wide synthetic with commercial utility [48] …”
Section: Nitration By Transition Metal‐free Catalystmentioning
confidence: 99%
“…Selective method for nitration of phenol and use of eco-friendly catalyst under mild condition make this approach wide synthetic with commercial utility. [48] Chaudhary et al reported an efficient protocol for nitration of N-alkyl anilines using tert-butyl nitrite (Scheme 40). For comparative study authors employed various solvents such as acetonitrile, tetrahydrofuran, methanol & 1,4-dioxane.…”
Section: Nitration By Transition Metal-free Catalystmentioning
confidence: 99%
“…It can be observed that the deviations of the enthalpy increased linearly with those of the entropy, the slope (T) being dimensionally a temperature. This and other statistical parameters were systematically analyzed for 10 homologous reaction series searched in the chemical literature [59][60][61][62][63][64]. Since it has been demonstrated [35][36][37] that the random errors of the activation enthalpy are directly proportional to those of the entropy, according to the equation:…”
Section: Effect Of Experimental Random Errors: a Critical Appreciationmentioning
confidence: 99%